Penerapan Metode Pembelajaran Positivisme Menggunakan Video Pembelajaran untuk Meningkatkan Hasil Belajar Siswa - Puspitasari, Anggraini Yussi; Anistyasari, Yeni; Harimurti, Rina (Jurnal Pendidikan Madrasah, 2024)
The application of positivism learning methods that focus on empirical experience and sensory observation provides a scientific foundation in the learning process. This study examines the effectiveness of using learning videos as a medium to support the positivism approach in improving student learning outcomes. Video media was chosen because of its ability to present abstract concepts to be more concrete, attract students' interest, and facilitate independent learning. The results of the study show that the integration of positivism methods with learning videos can significantly improve concept understanding, student engagement, and achievement of learning outcomes. These findings emphasize the importance of utilizing visual-based technology in conveying complex subject matter. The selection of relevant video content and interactive learning strategies can also maximize results. This approach offers great potential for educators to create a more effective and enjoyable learning experience for students.